Chapter Language as the user’s manual - Tabakowska, Elżbieta (Wydawnictwo Uniwersytetu Łódzkiego, 2025)
The author proposes that language be considered in terms of the user’s manual – both as a description of the instrument and as a set of instructions concerning its actual use. Assuming that the main function of man-created language is the description of man’s world, the argument follows the cognitive theory of language, stating that information processing which underlies language is embodied, embedded and enacted, and the fundamental property of language is its metonymic character. “The user’s manual of language” builds upon background knowledge, which enables proper completion of metonimies, which conditions understanding of messages. Discussing criteria used to differentiate between “literary” and “nonliterary” language within the proposed framework, the author analyses a number od examples to support the statement that cognition – also cognition via language – is embodied, embedded and enacted, an thus it crucially involves man’s interaction with the environment, as well as human affects and emotions. It cannot be objective, and the difference between “common language” and ”literary/poetic language” being quantitative rather than qualitative, it is a matter of degree.